Implementasi Nilai-Nilai Pancasila dalam Pelestarian Lingkungan Hidup di Indonesia - Abdusshomad, Alwazir (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to evaluate how Pancasila is applied in efforts to protect the environment in Indonesia, especially related to natural resource management, sustainable development, and harmonization between humans and nature. The method used is literature study, by examining various sources relevant to the theme. The research results show that Pancasila has a very important role in the development and life of Indonesia. As the basis of the state, Pancasila helps strengthen unity amidst the diversity of society. Pancasila values play a role in strengthening unity and meeting the needs of the nation, as well as having a significant impact on the character formation of the younger generation. Implementation of Pancasila values can also support sustainable management of natural resources and achieve development in accordance with the character and values of Indonesian society, as well as preserving nature for future generations.